Active vs. passive recovery during high-intensity training influences hormonal response - Wahl, P.; Mathes, S.; Achtzehn, S.; Bloch, W.; Mester, J. (International Journal of Sports Medicine, 2014)
The aim of the present study was to compare the effects of active (A) vs. passive (P) recovery during high-intensity interval training on the acute hormonal and metabolic response. Twelve triathletes/cyclists performed four 4 min intervals on a cycle ergometer, either with A- or P-recovery between each bout. Testosterone, hGH, cortisol, VEGF, HGF and MIF were determined pre, 0', 30', 60' and 180' after both interventions. Metabolic perturbations were characterized by lactate, blood gas and spirometric analysis. A-recovery caused significant increases in circulating levels of cortisol, testosterone, T/C ratio, hGH, VEGF and HGF. Transient higher levels were found for cortisol, testosterone, hGH, VEGF, HGF and MIF after A-recovery compared to P-recovery, despite no differences in metabolic perturbations. A-recovery was more demanding from an athlete`s point of view. Based on the data of testosterone, hGH and the T/C-ratio, as well as on the data of VEGF and HGF it appears that this kind of exercise protocol with A-recovery phases between the intervals may promote anabolic processes and may lead to pro-angiogenic conditions more than with P-recovery. These data support the findings that also the long term effects of both recovery modes seem to differ, and that both can induce specific adaptations.